Some Best Proximility Coincidence Point Theorems for G-Proximal Geraghty Contraction Type M Mapping in Complete Metric Space endowed with Directed Graphs: Supreedee Dangskul, Phakdi Charoensawan - Team, Support (Thai Journal of Mathematics, 2022)
In this study, we proved the existence of best proximility coincidence point for $G$-Proximal Geraghty type M mapping in a complete metric spaces endowed with directed graph. We also give some example to support our result. Moreover, we apply our main result to several consequences and for the case of metric spaces endowed with symmetric binary relations.